PICU associated social-emotional adversity in early childhood cancer patients: consequences in neurodevelopment and mental health - Kroupina, Maria; Parker-McGowan, Quannah; Kotz, Madeline; Somani, Arif (Frontiers in Oncology, 2026)
Here we propose that PICU hospitalization accentuates extreme early social-emotional adversity and compounds hospital-associated trauma that may result in neurodevelopmental and mental health challenges for pediatric cancer survivors. We focus specifically on the first three years of life, when the incidence of childhood cancer is the highest and the brain is in its most vulnerable period of development. A comprehensive understanding of risks associated with PICU hospitalization is necessary for informing improvements to the inpatient environment and proposing new models for administering mental health care, evidence-based intervention, and long-term follow-up.